The Effect Of Gender Diversity And Free Cash Flow On Dividend Policy With Firm Size As A Moderating Variable - Dita Mariska Candra Darusman; Widiasmara, Anny (Politeknik Negeri Madiun, 2024)
The purpose of this study was to determine the effect of gender diversity and free cash flow on dividend policy with firm size as a moderating variable. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2020-2023. This study used purposive sampling technique, so 138 data were obtained from 87 mining companies listed on the Indonesia Stock Exchange. The results showed that gender diversity has no effect on dividend policy, free cash flow has a significant positive effect on dividend policy. Firm size cannot moderate the effect of gender diversity and free cash flow on dividend policy. The implications of the results of this study are expected to provide information for consideration by stakeholders such as the board of directors and as information for investors in making investment decisions.